1997
DOI: 10.1126/science.276.5318.1560
|View full text |Cite
|
Sign up to set email alerts
|

Substantial Genetic Influence on Cognitive Abilities in Twins 80 or More Years Old

Abstract: General and specific cognitive abilities were studied in intact Swedish same-sex twin pairs 80 or more years old for whom neither twin had major cognitive, sensory, or motor impairment. Resemblance for 110 identical twin pairs significantly exceeded resemblance for 130 fraternal same-sex twin pairs for all abilities. Maximum-likelihood model-fitting estimates of heritability were 62 percent for general cognitive ability, 55 percent for verbal ability, 32 percent for spatial ability, 62 percent for speed of pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

32
394
4
5

Year Published

1998
1998
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 654 publications
(435 citation statements)
references
References 19 publications
32
394
4
5
Order By: Relevance
“…Consistent with this finding, longitudinal twin and family studies and studies of older twins show that genetic effects on general intelligence increase over time (McClearn et al, 1997;Plomin, Fulker, Corley, & DeFries, 1997;Wilson, 1983). It has also been shown that environmental influences on mental development beyond childhood appear to be those that are not shared by family members.…”
Section: Introductionmentioning
confidence: 60%
“…Consistent with this finding, longitudinal twin and family studies and studies of older twins show that genetic effects on general intelligence increase over time (McClearn et al, 1997;Plomin, Fulker, Corley, & DeFries, 1997;Wilson, 1983). It has also been shown that environmental influences on mental development beyond childhood appear to be those that are not shared by family members.…”
Section: Introductionmentioning
confidence: 60%
“…Clearly, classic tests of heritability (that is, comparisons of deficits in related individuals at varying levels of genetic risk, optimally between monozygotic and dizygotic twin pairs) have not been done for some of the so-called schizophrenia-associated intermediate phenotypes, but for others, the evidence is good. Cognitive functions related to aspects of memory, speed of processing, attention and IQ are highly heritable in the human species (with evidence from twin studies), 3,6,9 though measures on every cognitive test do not show strong heritability results, in some instances more likely because of the psychometrics of the test than the cognition involved. 10 Several cognitive abnormalities associated with schizophrenia are found with increased prevalence in healthy siblings of patients with schizophrenia, including healthy monozygotic co-twins, and the evidence from twin studies suggests that the cognitive deficits related to IQ, working memory and attention are heritable traits.…”
Section: Are So-called Intermediate Phenotypes Heritable?mentioning
confidence: 99%
“…Episodic memory is a heritable (e.g., McClearn et al, 1997) and polygenic (Papassotiropoulos and de Quervain, 2011) trait. We explore whether genetic predispositions of dopaminergic and glutamatergic neuromodulation interactively influence episodic memory in younger and older adults.…”
Section: Introductionmentioning
confidence: 99%